Teenage marriage, fertility, and well-being: Panel evidence from India - Singh, A; Espinoza Revollo, P (Young Lives, 2016)
This paper uses a unique dataset from Andhra Pradesh, tracking a cohort of children who were born in 1994–95 from the ages of 8 to 19 years, to ask three key questions about teenage marriage and fertility in India. First, what predicts getting married during the teen years? Second, what predicts having given birth by 19? And third, do the subjective wellbeing and psychosocial outcomes such as the agency, self-efficacy, and self-esteem of married young women differ from those of their unmarried peers — and to what extent can these differences be accounted for by differing socio-economic status and characteristics of, and investments in, their parental household? Our analysis is novel because such long-term panel data, linking backgrounds and investments in the natal household with welfare outcomes and socio-emotional measures in the marital household, have not previously been available in this setting.